An Innovative Strategy Based on Dynamic Programming to Solve Power Flow Problems in Radial Electric Distribution Systems - Marinho, Max R. [UNESP] (2025)
In this work, a new strategy based on dynamic programming is proposed to solve the power flow (PF) problem in radial distribution systems using the backward/forward sweep method (BFSM). The strategy consists of a dynamic tree of varied children to represent the radial configuration of the system, allowing a new way of storing and accessing the system information for the PF calculation. This strategy avoids both the bus renumbering procedure for branch ordering used in different BFSMs (due to their branch-oriented characteristic) and the matrix inversion procedure, also used in different BFSMs. The proposed strategy is innovative, since PF problems have been solved in the literature by methods based on static programming. Tests with 14-bus, 33-bus, 84-bus, 136-bus, and 417-bus systems were carried to evaluate both the performance of the construction procedure of the dynamic tree in comparison to the classical branch ordering procedure and the performance of the PF calculation procedure using the proposed dynamic tree in contrast to traditional BFSMs. Promising results were obtained in both evaluated aspects. Therefore, this work contributes to the opening of new studies for a dynamic approach aimed at calculating the PF in radial distribution systems.